Moving in a Box: Improving Spatial Orientation in Virtual Reality using Simulated Reference Frames - Nguyen-Vo, Thinh; Riecke, Bernhard E.; Stuerzlinger, Wolfgang (IEEE Symposium on 3D User Interfaces 3DUI, 2017)
Despite recent advances in virtual reality, locomotion in a virtual environment is still restricted because of spatial disorientation. Previous research has shown the benefits of reference frames in maintaining spatial orientation. Here, we propose using a visually simulated reference frame in virtual reality to provide users with a better sense of direction in landmark-free virtual environments. Visually overlaid rectangular frames simulate different variations of frames of reference. We investigated how two different types of visually simulated reference frames might benefit in a navigational search task through a mixed-method study. Results showed that the presence of a reference frame significantly affects participants' performance in a navigational search task. Though the egocentric frame of reference (simulated CAVE) that translates with the observer did not significantly help, an allocentric frame of reference (a simulated stationary room) significantly improved user performance both in navigational search time and overall travel distance. Our study suggests that adding a variation of the reference frame to virtual reality applications might be a cost-effective solution to enable more effective locomotion in virtual reality.
Keywords: 2-page conference paper; Riecke; Riecke_2017; bernhard-riecke; conferencePaper; conferencePapers; iat802; iat802_fall2016; leaning-based interfaces; motion-cueing; navi-search-in-VR; naviChair; proj--motionCueingInterfaces; proj--naviSearchInVR; short conference paper; thinh-nguyen-vo; wolfgang-stuerzlinger